Apple Advertisement. (Computer (00189162), 2012)
The article reports on the job vacancies at Apple Inc. in Cupertino, California as of May 2012. It highlights the professionals needed by the company which include software engineers and application-specific integrated circuit (ASIC) design engineer. Qualified individuals are requested to mail their resumes at the company's address.